Prevalence of Fasciola Gigantica in Cattle and Sheep Slaughtered at the Eldoret Slaughterhouse, Kenya (International Journal of Scientific Research in Science and Technology, 2025)
Fasciolosis impact livestock production globally, particularly in Sub-Saharan Africa, necessitating studies to develop intervention strategies. The objectives of the current study were The main objective of the study was to determine the prevalence of Fasciola gigantica in cattle and sheep slaughtered at the Eldoret Slaughterhouse in Kenya with a null hypothesis of Ho1: There is no Fasciola gigantica in cattle and sheep slaughtered at the Eldoret Slaughterhouse in Kenya. The livestock traders are not aware of the nutritional depletion associated with fasciola and hydatid cyst. From 3rd May,2024 to 3rd June, 2024, a 30-day study was carried out at the Eldoret Slaughterhouse on cattle and sheep slaughtered. The study was carried out on a total of 479 cattle and 313 sheep which were examined in 30 days. The results at the slaughter house revealed a high Fasciola gigantica prevalence of 64.8% in cattle and 33.2% in sheep. There were higher detection rates in bile compared to faecal samples. In Conclusion there was high prevalence of fasciola gigantica and hydatid cyst in cattle compared to sheep. Recommendations include Implementing a comprehensive parasite control program, including regular deworming of livestock with effective fasciolicides. Improving pasture management to reduce the risk of Fasciola gigantica infection, such as fencing off wet areas and providing clean drinking water sources. Educating farmers on the lifecycle of Fasciola gigantica and preventive measures they can take to reduce infection rates in their herds and flocks. Conducting regular monitoring and surveillance of fasciolosis in livestock to track the effectiveness of control measures over time.